Spatial-temporal changes of NDVI in the three northeast provinces and its dual response to climate change and human activities - Wu, Rina; Wang, Yan; Liu, Buyun; Li, Xueming (Frontiers in Environmental Science, 2022)
As the most important ecological barrier in eastern China, the three northeast provinces have extraordinary ecological significance. Their geographical location and climatic conditions make the distribution pattern of vegetation unique. Among them, climate change and human activities are the main factors affecting the richness and complexity of vegetation, climate change dominates the overall pattern of vegetation distribution, and regional human intervention locally changes the growth state of vegetation. Therefore, based on NDVI data of vegetation, meteorological data and socio-economic data,statistical methods such as Sen’s slope estimator, Mann-Kendall trend test, center of gravity transfer model, Hurst index and coefficient of variation were adopted to analyze the spatio-temporal changes and future trends in vegetation coverage; The use of Geographic detector to understand the relationship between NDVI to climate change and human activities. The results suggested that: (1) The three northeast provinces of China experienced an overall increasing NDVI at a rate of 0.016%/year from 2001 to 2020. The NDVI shows intensive heterogeneity in space, exhibiting a landscape of high in the East, low in the west, high in the north and low in the south; (2) The results of geographic detectors show that the temporal and spatial distribution pattern of vegetation NDVI is mainly determined by ≥ 10 ℃ accumulated temperature, ≥ 0 ℃ accumulated temperature, annual average temperature and land use type. The interaction between factors presents a bi-variable enhancement and nonlinear enhancement , and human activity factors enhance the contribution of climate factors. (3) Future changes in NDVI indicated that the vegetation coverage showed a trend of "overall improvement and regional degradation" from 2001 to 2020, and showed reverse persistence. The degraded area of vegetation will be more than the improved area. The research results will help the three northeast provinces cope with global climate change, enrich the research on the vegetation in the three northeastern provinces, and provide a scientific basis for formulating appropriate regional ecological protection policies.